2018
DOI: 10.7717/peerj.4166
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects ofSalvia officinalisleaf extract on insulin resistance and inflammation in a model of high fat diet-induced obesity in mice that responds to rosiglitazone

Abstract: BackgroundSalvia officinalis (sage) is a native plant to the Mediterranean region and has been used for a long time in traditional medicine for various diseases. We investigated possible anti-diabetic, anti-inflammatory and anti-obesity effects of sage methanol (MetOH) extract in a nutritional mouse model of obesity, inflammation and insulin resistance, as well as its effects on lipolysis and lipogenesis in 3T3-L1 cells.MethodsDiet-induced obese (DIO) mice were treated for five weeks with sage methanol extract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…ME showed similar effects to SIM and their combination. ME improved tissue insulin resistance, glucose levels and reduced body weight gain in HFD fed rats, which supports previous studies using polyphenol-rich plant extracts [28,29]. Insulin and glucose regulate leptin levels.…”
Section: Discussionsupporting
confidence: 89%
“…ME showed similar effects to SIM and their combination. ME improved tissue insulin resistance, glucose levels and reduced body weight gain in HFD fed rats, which supports previous studies using polyphenol-rich plant extracts [28,29]. Insulin and glucose regulate leptin levels.…”
Section: Discussionsupporting
confidence: 89%
“…Favorably, administration of rosemary extract resulted in pronounced reduction in serum TNF-α and IL-1β, indicating its anti-inflammatory behaviors. This finding is in agreement with previous studies that reported the ability of rosemary to decrease circulating levels of TNF-α in hyperammonemic rats (Lopez-Nova et al, 2012;Ozbek, 2012;Bekker et al, 2016 andBen Khedher et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Administration of either SEO or simvastatin to HFD‐treated mice was found to reduce dietary intake, as compared to the control group. Earlier, Ben Khedher et al () have shown that administration of Salvia officinalis leaf extract at a low dose (100 mg/kg body weight) to HFD fed mice provokes a reduced feed intake. According to these authors, this could be due to a decrease in the plasma levels of ghrelin, “the hunger hormone.” Indeed, the latter is a 28 amino acid peptide found in the stomach and the hypothalamus, as reported by Date et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Administration of either SEO or simvastatin to HFDtreated mice was found to reduce dietary intake, as compared to the control group. Earlier, Ben Khedher et al (2018) have shown that administration of Salvia officinalis leaf extract at a low dose (100 mg/ kg body weight) to HFD fed mice provokes a reduced feed intake.…”
Section: Discussionmentioning
confidence: 99%